Closed Encounters : Literary Politics and Public Culture - Wallen, Jeffrey (Book collections on Project MUSE., 1998)
In a provocative and fair-minded look at current critical practices and the future of the academy, Jeffrey Wallen draws a disturbing picture of public intellectuals in search of a public and cultural critics unable to enter a dialogue with others. Taking up several of the most influential critics of recent years-Edward Said, Eve Kosofsky Sedgwick, Michael Berube, Gerald Graff, Richard Rorty, Stanley Fish, and many others-Wallen explores the intersections between literary and actual politics.